Recessive mutations in a distal PTF1A enhancer cause isolated pancreatic agenesis. - Weedon,MN; Cebola,I; Patch,A-M; Flanagan,SE; De,Franco E; Caswell,R; Rodríguez-Seguí,SA; Shaw-Smith,C; Cho,CH-H; Allen,HL; Houghton,JA; Roth,CL; et al. (Nature genetics, 2014)
The contribution of cis-regulatory mutations to human disease remains poorly understood. Whole-genome sequencing can identify all noncoding variants, yet the discrimination of causal regulatory mutations represents a formidable challenge. We used epigenomic annotation in human embryonic stem cell (hESC)-derived pancreatic progenitor cells to guide the interpretation of whole-genome sequences from individuals with isolated pancreatic agenesis. This analysis uncovered six different recessive mutations in a previously uncharacterized ~400-bp sequence located 25 kb downstream of PTF1A (encoding pancreas-specific transcription factor 1a) in ten families with pancreatic agenesis. We show that this region acts as a developmental enhancer of PTF1A and that the mutations abolish enhancer activity. These mutations are the most common cause of isolated pancreatic agenesis. Integrating genome sequencing and epigenomic annotation in a disease-relevant cell type can thus uncover new noncoding elements underlying human development and disease.